Transformasi Digital dalam Pengembangan UMKM Berbasis Syariah di Gorontalo - Ansar Sahabi; Laras Ayu Sekarrini; Ditya Zul Asmi; Mohamad Rinaldi Djakaria; Silvy Windha Mediaswari (Politeknik Kebangsaan, 2026)
Digital transformation has become a crucial factor in enhancing the competitiveness of Micro, Small, and Medium Enterprises (MSMEs), including those based on Islamic economic principles. This study aims to analyze the development of digital transformation in the growth of Sharia-based MSMEs in Gorontalo Province. The research employs a quantitative descriptive approach using secondary data obtained from the Central Bureau of Statistics (BPS), government reports, and relevant academic publications. The results indicate that the adoption of digital technology among MSMEs in Gorontalo has increased, although several challenges remain, such as limited digital literacy, access to Islamic financing, and technological infrastructure. From an Islamic economic perspective, digital transformation can promote more transparent, fair, and sustainable business practices. Therefore, collaboration between government, Islamic financial institutions, and MSME actors is essential to strengthen the Sharia-based digital ecosystem